Effect of mechanical brushing during the nursery on the growth and development of tomato plants - LI Guo-jing; ZHANG Wei-zhang; Benoit F; Ceustermans N (浙江大学学报. 农业与生命科学版, 2002)
The internodes length of seedlings is of important during propagation and planting. One of the most common methods of retarding stem elongation is the application of chemical plant growth regulators. Whereas it is not legal on vegetables in many countries today because of the potential danger of chemical residues. In the present experiments, a practicable Mechanical Brusher was constructed. They were expected to demonstrate how Mechanical Brushing（MB）might be applied to produce compact seedlings instead of the application of chemical growth retardants.